2019
DOI: 10.1002/qj.3515
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPM high‐frequency microwave measurements with radiative transfer simulation under snowfall conditions

Abstract: The Global Precipitation Mission (GPM) Microwave Imager (GMI) has four channels at 166 and 183 GHz that provide critical information on snow precipitation. Since the applications of these high‐frequency microwave channels to snowfall prediction and retrieval are still in a very early stage, it is important to evaluate the biases between observed and simulated brightness temperatures for those channels under snowfall conditions. A radiative transfer model that supports the computation of single‐scattering prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…On the ground, weather radars are typically used to estimate precipitation but are also extensively used for research purposes. Furthermore, Doppler radars have demonstrated capabilities to both identify and quantify different water phases in mixed-phase cloud (Shupe et al, 2004), while multi-frequency radars have shown capabilities to retrieve information related to the shape of the ice particles (Kulie et al, 2014;Kneifel et al, 2015;Yin et al, 2017;Leinonen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the ground, weather radars are typically used to estimate precipitation but are also extensively used for research purposes. Furthermore, Doppler radars have demonstrated capabilities to both identify and quantify different water phases in mixed-phase cloud (Shupe et al, 2004), while multi-frequency radars have shown capabilities to retrieve information related to the shape of the ice particles (Kulie et al, 2014;Kneifel et al, 2015;Yin et al, 2017;Leinonen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, correctly simulating brightness temperatures is needed for physical snowfall retrievals as well as data assimilation of radiance observations in numerical weather prediction models. Yin and Liu (2019) has studied the bias characteristics of observed minus simulated brightness temperatures at high frequency channels of Global Precipitation Measurement Microwave Imager (GPM/GMI) under snowfall conditions. In their study, a radiative transfer model that includes single-scattering properties of nonspherical snow particles is used to simulate brightness temperatures at 89 through 183 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Also, numerical weather prediction can typically not predict small-scale cloud structures, making comparisons between simulated and real observations difficult at such scales. This issue can be circumvented by using radar reflectivity fields as input to the forward model (Bennartz and Bauer, 2003;Skofronick-Jackson et al, 2008;Kulie et al, 2010;Yin and Liu, 2019;Ringerud et al, 2019), ensuring that small-scale cloud structures are properly resolved and represented. Lidar measurements can be used in a similar way, as the already mentioned study by Fox et al (2019) is an example of.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of measurements by radar requires that the reflectivity fields are converted to fields of ice water content (IWC) (i.e., mass density of ice hydrometeors). The recent study by Yin and Liu (2019) assessed GMI measurements by comparing them to forward simulations derived from collocated CloudSat measurements, using a selection of different non-spheroidal particle models. In general, good agreement was attained, especially for the aggregate particle type used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation